Estimation of Radioactivity in Dash - Salakhli Bentonite Clay: Depth and Radionuclide Migration Processes - Akhmedov E. A. (BIO Web of Conferences)
This paper examines the assessment of radioactivity in the Dash- Salahly bentonite clay with a focus on depth-dependent radioactivity variations within the deposit. The study included determination of the specific effective activity of various radionuclides in soil samples collected from different depths. The results highlight that the high radioactivity of bentonite clay is primarily due to elevated levels of potassium-40 (K-40), with the highest specific activity observed at depths of 5 m, 10 m, 20 m and 25 m. Additionally, the paper compares the radioactivity levels of other radionuclides such as radium-226 (Ra-226) and thorium-234 (Th-234), noting that Ra-226 exhibits significant activity at depths of 5 m, 10 m, 15 m and 25 m, while Th-234 exhibits higher activity at depth of 20 m. These results contribute to a better understanding of radionuclide migration patterns in bentonite clay and the potential implications for environmental safety and management.